Open Loop and Closed Loop Performance of Switched Reluctance Motor with Various Converter Topologies - Malligunta Kiran Kumar; G.R.K. Murthy; S S Srinivas.Addala (Institute of Advanced Engineering and Science, 2014)
Switched reluctance motor (SRM) is becoming popular because of its simple construction, robustness and low-maintenance. This motor is very useful for high speed applications because no windings are placed on rotor and can also be used for variable speed applications in industries. Converter is one of the important elements in SRM which plays a very crucial role. In this paper various converter topologies for 6/4 switched reluctance motor and Asymmetric bridge converter topology for 8/6 switched reluctance motor are discussed. Finally a closed loop for each converter topology is proposed. The converter topologies are simulated by using MATLAB/SIMULINK. Constant speed is achieved in closed loop control.DOI: http://dx.doi.org/10.11591/ijpeds.v5i1.6133